Proceedings (Management and Connections Journal, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2013.2.1.5927.1-4.Presents the second edition of the Management and Connections Journal (Revista Gestão & Conexões), v2, n1, jan./jun. 2013.